Efektivitas Hatha Yoga Terhadap Kesehatan Fisik - Ni Wayan Yusi Armini; Ida Ayu Diah Larashanti (UHN IGB Sugriwa Denpasar, 2020)
Today, humans are faced with life problems that are so tight with competition and competition in various aspects, so that it gives birth to a high tension culture. Tension that occurs causes disrupted anatomy of the body, even damage that causes balance of body and mind problems. This disharmony is a disease that many people face, namely stress, a psychosomatic disorder that can only be cured through inward healing, namely relaxation. Yoga is a method of self-discipline that has been applied and yoga also hits sports today, a sport that is very easy to use and at any time can and does not require a lot of space. So that yoga is made a healthy lifestyle trend that is not only recognized in the eastern hemisphere, especially for Hindus but also in the western world, which shows the universality of the teachings of Yoga itself that can be applied by anyone. One type of yoga that is famous in the world is Hatha Yoga. Hatha Yoga is one way of connecting with Iswara (God Almighty) by forming perfect harmony between the two pranic streams found in the body through the practice of Asana, Pranayama, Mudra and Bandha. So that Hatha Yoga is able to provide relaxation to the body and mind that will create physical and spiritual health.